Multimedia products in impressions economics - Pushkar, Oleksandr; Kurbatova (Tataryntseva), Yuliia (Eurasian Social Sciences Association, 2016)
The external factors influencing the perception were selected by generalization method: the concept of the project; structure and navigation; quality of content; technical equipment; and of internal factors: the value of the user; perception; type of perception. The essence of creating a multimedia product is the transfer of ideas embedded by developer. Authors have developed a classification of user ideas perception on the basis of perception time and emergence of ideas zones. In the article it is purposed to make the decisions on the interactivity necessity based on user activity analysis and purpose of multimedia product developer.
Keywords: multimedia product; economy experiences; factors; perception